Concepciones populares sobre soledad de los adultos mayores de España y Bucaramanga, Colombia (2011)
The goal of the following article is to compare the concepts of loneliness in the elderly people of Spain and the elderly people of Bucaramanga, Colombia; this involved the use of a comparative qualitative design of the results of the "Conception of Loneliness Survey" against item 16 of the questionnaire "The loneliness of the elderly". The sample consisted of 1956 Spanish elders and 6607 of Bucaramanga, Colombia. A minimum age of 65 was held as a constant between both samples. The results showed a predominant negative conception of loneliness, high incidence of family related conceptions, categories referencing isolation (objective solitude) and loneliness (subjective solitude), and positive concepts in the Colombian sample.